Analytical Study on Work Satisfaction of the University Faculty Members in Kurdistan Region - M. Prabhu; Ahmed Talaat Jabbar (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Threr are four factors for production which is (Land, labour, capital and organisation). Financial capital is considered as the backbone of economic growth of any nation. It has been spontaneously propagated to enhance the flow of capital to boost the level of economic growth in developing countries to address the problems of the low standard of living, poverty and unemployment. The main objective for the study is to assess the level of work satisfaction of the university faculty members in Kurdistan Region. The proposed research is descriptive in nature. The research endeavors to describe the personal characteristics of faculty members surveyed and assess their level of satisfaction with their work and the working environment. This research is based purely on primary data, collected using the survey method. Sample size for this study shall be 309 respondents. The Simple Random sampling technique was used to select the faculty members comprising of Lecturers, Professors, Assistant Lecturers and Assistant Professors from 30 Private and 28 Government Universities in Kurdistan. The results reveal that faculty members display a reasonable level of satisfaction towards interpersonal relationships prevalent in the University as the overall mean hover around the 3.6 mark in five point scale which is above average. The faculty members have a good level of satisfaction towards relationships with supervisors, The Work, Environment, Competency, Recognition and Salary are quite moderate.